PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS PELANGGAN PENGGUNA KARTU TELKOMSEL PADA MAHASISWA - Viviani Aryantika Simbolon; Khoirunnisa Br Ritonga; Ria Tania; Amelia Zahra; Dian Sukmawati (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This study aims to (1) to determine the influence of brand image and brand trust influence partially to customer loyalty (2) to know the influence of brand image and brand trust influence simultaneously to customer loyalty (3) to know among brand image and brand belief most Dominant effect on customer loyalty. The method used in this research is quantitative method. Theresult of research is multiple linear regression equation Y = 1,328 + 0,340 + 0,264 + e. partially brand image have positive significant effect with value equal to 3,352, equal to 1,988, brand trust have significant positive effect with value equal to 2,607 equal to 1,988. Simultaneously brand image and brand trust influence to customer loyalty with value equal to 14,402, sebasar 3,10. The most dominant variable in this research is brand image with value 3,352.